Crucifixes Found Underneath the Dubrovnik Cathedral (Archaeologia Adriatica, 2017)
The numerous numismatic items found during the excavations underneath the Dubrovnik Cathedral led by Josip Stošić in the 1980s included around 60 saint and pilgrim medallions and small crucifixes/crosses from the 16th and 17th centuries. The article analyzes the crucifixes – grave goods from Graves 21 and 22.
Keywords: Dubrovnik Cathedral; grave goods; crucifix/cross pendants